2019
DOI: 10.1182/bloodadvances.2019000729
|View full text |Cite
|
Sign up to set email alerts
|

Sptlc1 is essential for myeloid differentiation and hematopoietic homeostasis

Abstract: Key Points Sptlc1 is essential for myeloid differentiation during hematopoiesis; ER stress prevents myeloid development in Sptlc1 mutant mice. Accumulation of fatty acid promotes ER stress in Sptlc1 mutant myeloid progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Molecular analysis indicates that aberrant myelopoiesis is accompanied by endoplasmic reticulum stress. These phenotypes are similar to the defects observed in Sptlc1 null mutants ( 30 ). On the other hand, germline null mutants of ssSPTb are homozygous viable and do not show defects in adult hematopoiesis.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…Molecular analysis indicates that aberrant myelopoiesis is accompanied by endoplasmic reticulum stress. These phenotypes are similar to the defects observed in Sptlc1 null mutants ( 30 ). On the other hand, germline null mutants of ssSPTb are homozygous viable and do not show defects in adult hematopoiesis.…”
supporting
confidence: 84%
“…The comparison of the sphingolipid profile between ssSPTa +/+ and ssSPTa −/− described above suggests that SSSPTA plays a major role in the de novo biosynthesis of sphingolipids in the adult hematopoietic system. As with Sptlc1 −/− BMCs, we see a correlation between loss of SSSPTA function, significant decrease in major sphingolipids, and defective myelopoiesis in the BMCs ( 30 ). It is likely that SSSPTA is a critical component of the SPT complex in mammalian adult hematopoietic system.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Similarly, disruption of sphingolipid biosynthesis caused by the deletion of SPT long-chain subunit1 (SPTLC)1 or SPTLC2 caused mouse embryonic lethality ( 10 ). Furthermore, it was shown that 1) disruption of de novo sphingolipid synthesis in SPTLC2 heterozygous mice led to bronchial hyperreactivity in the absence of inflammation ( 11 ), 2) inducible deficiency of SPTLC2 in the intestine caused death of mice within ten days upon tamoxifen treatment ( 12 ), and 3) conditional knockout of SPTLC1 subunit in the adult bone marrow affected myeloid differentiation ( 13 ). In contrast, increased sphingolipid levels observed in the brain of ORMDL1 and ORMDL3 double KO (ORMDL1, 3 dKO) mice were linked to the defects in littermate size, disruption of proper myelination, and a neurologic phenotype ( 9 ).…”
Section: Introductionmentioning
confidence: 99%